The relationship between jealousy and aggression : a review of literatures related to wives' aggression. - Edalati, Ali; Redzuan, Ma’rof (EuroJournals Publishing, Inc., 2010)
This paper reviews several empirical studies which highlight the relationship between jealousy and aggression. Jealousy is indicated as a factor contributing to male and female aggression and it is almost universal, found almost in every culture. Research showed that women were more jealous than men. Male jealousy is triggered by sexual infidelity while female jealousy is triggered by emotional infidelity. According to social learning theory, women learn different relational strategies than men by observing other woman using those strategies. A strong relationship between jealousy and aggression has been reported in several past studies. Based on the findings of many studies, there is a significant relationship between jealousy and aggression, such as loss of fondness, refusal, distrustful, lack of self-confidence, sentimental support, decreased feeling of incomparability and fear. Similarly, there are a number of important findings which indicated that jealousy has a high relationship with aggression. In addition, jealousy may play a role in aggression between couples, and jealousy is a cause for aggression after marriage. Thus, this paper aims to review the relationship between jealousy and aggression